2005
DOI: 10.1182/blood-2004-05-1916
|View full text |Cite
|
Sign up to set email alerts
|

Gi-independent macrophage chemotaxis to lysophosphatidylcholine via the immunoregulatory GPCR G2A

Abstract: G2A is a G-protein–coupled receptor (GPCR) involved in immune regulation. Previous studies have shown that lysophosphatidylcholine (LPC), a bioactive lipid associated with atherosclerosis and autoimmunity, acts through G2A to induce diverse biologic effects. Production of LPC during cell apoptosis serves as a chemotactic signal for macrophage recruitment. Here we demonstrate that macrophage chemotaxis to LPC is dependent on G2A function. Wild-type but not G2A-deficient mouse peritoneal macrophages migrated tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 57 publications
3
133
1
2
Order By: Relevance
“…Indeed, several G protein-coupled receptors, including G2A and GPR4, have been reported to bind to LPC (Xu, 2002;Meyer zu Heringdorf et al, 2002). LPC induces chemotaxis of macrophages through activation of G2A (Yang et al, 2005), and anti-G2A antibody attenuates protective Figure 4. Effects of LPC-stimulated PLD2 activity on the serum starvation-induced apoptosis in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several G protein-coupled receptors, including G2A and GPR4, have been reported to bind to LPC (Xu, 2002;Meyer zu Heringdorf et al, 2002). LPC induces chemotaxis of macrophages through activation of G2A (Yang et al, 2005), and anti-G2A antibody attenuates protective Figure 4. Effects of LPC-stimulated PLD2 activity on the serum starvation-induced apoptosis in PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…G2A-knockout mice have increased susceptibility to atherosclerosis and develop late-onset autoimmunity (31). These phenotypes are thought to arise from disruption of G2A-dependent modulation of immune cell function including differentiation and chemotaxis (62,(64)(65)(66)(67)(68)(69)(70)(71). This suggests that Bacteroides spp.…”
Section: Comparative Phylogenetic and Functional Analysis Of Effectormentioning
confidence: 99%
“…Macrophage G2A Signaling-We have recently reported that lyso-PS can signal through the G proteincoupled receptor, G2A, for calcium flux (20), and G2A has been recently described as a receptor on macrophages responsible for mediating macrophage chemotactic responses (50,51). Accordingly, G2A appeared to be a reasonable candidate for lyso-PS-dependent enhancement of apoptotic cell engulfment.…”
Section: Lyso-ps Enhances Ps-dependent Engulfment Of Apoptotic Cells mentioning
confidence: 99%